2015
DOI: 10.1007/s40259-015-0147-0
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Biosimilar Design and Development: Implications for Policies and Stakeholders

Abstract: Biosimilars are required to be similar or highly similar in structure to their biologic reference product but are neither expected nor required to contain identical active substances. For example, glycosylated biosimilars approved to date demonstrate quantitative and qualitative structural differences from their reference product and exemplify the latitude of variations permitted for biosimilars. Although differences between a candidate biosimilar and its reference product will be evaluated for differential cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…In contrast, rather than being interchangeable, prescribers should consider biosimilars 'individual therapeutic alternatives'. 6 Indeed, the Medicines and Healthcare products Regulatory Agency (MHRA) recommends prescribing all biopharmaceuticals, including biosimilars, by brand. So, unlike generics, a pharmacist cannot substitute an alternative.…”
Section: Subtle Differencesmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, rather than being interchangeable, prescribers should consider biosimilars 'individual therapeutic alternatives'. 6 Indeed, the Medicines and Healthcare products Regulatory Agency (MHRA) recommends prescribing all biopharmaceuticals, including biosimilars, by brand. So, unlike generics, a pharmacist cannot substitute an alternative.…”
Section: Subtle Differencesmentioning
confidence: 99%
“…For example, changes in glycosylation (specifically increased N-glycan branching and sialylation) seem to increase the potency of epoetin, primarily by altering half-life. 6 In another example, a biosimilar manufacturer used a genetically engineered yeast to produce growth hormone. The original product was derived from genetically engineered Escherichia coli.…”
Section: Subtle Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…This was clearly demonstrated by a recent evaluation of glycosylated biosimilars approved in the EU and Japan. It was shown that differences in N-glycosylation not only exist between a biosimilar and a single originator product, but also exists among the different biosimilar products [41].…”
Section: Introductionmentioning
confidence: 99%